Constraining Cyclic Peptides To Mimic Protein Structure Motifs. Issue 48 (6th October 2014) - Hill, Timothy A.; Shepherd, Nicholas E.; Diness, Frederik; Fairlie, David P.
Abstract Many proteins exert their biological activities through small exposed surface regions called epitopes that are folded peptides of well‐defined three‐dimensional structures. Short synthetic peptide sequences corresponding to these bioactive protein surfaces do not form thermodynamically stable protein‐like structures in water. However, short peptides can be induced to fold into protein‐like bioactive conformations (strands, helices, turns) by cyclization, in conjunction with the use of other molecular constraints, that helps to fine‐tune three‐dimensional structure. Such constrained cyclic peptides can have protein‐like biological activities and potencies, enabling their uses as biological probes and leads to therapeutics, diagnostics and vaccines. This Review highlights examples of cyclic peptides that mimic three‐dimensional structures of strand, turn or helical segments of peptides and proteins, and identifies some additional restraints incorporated into natural product cyclic peptides and synthetic macrocyclic peptidomimetics that refine peptide structure and confer biological properties.